Shift in subsistence crop dominance from broomcorn millet to foxtail millet around 5500 BP in the western Loess Plateau - Yang, Yishi; Wang, Jia; Li, Gang; Dong, Jiajia; Cao, Huihui; Ma, Minmin; Chen, Guoke; Dong, Guanghui (Frontiers in Plant Science, 2022)
Broomcorn and foxtail millet were the most important crops in Neolithic north China. Although the significance of broomcorn millet in human subsistence exceeded that of foxtail millet during the early Neolithic, this pattern was reversed by the end of Neolithic period. However, the process underlying this shift remains unclear. The recent excavation of the Gedachuan (GDC) in Zhangjiachuan county has revealed an abundance of relics including millet crop remains from relatively continuous strata of the Yangshao and Qijia cultures, and therefore provides a unique opportunity to examine how and when foxtail millet replaced broomcorn millet as the dominant crop in the western Loess Plateau during the Neolithic period. In this study, we identify 1738 and 2686 broomcorn and foxtail millet remains, respectively, from 74 flotation samples, accounting for 38.81% and 59.98% of total plant remains, respectively. Compared with 23 direct dates of carbonized crop grains in GDC, we propose that the weight of foxtail millet in plant subsistence of GDC first exceeded that of broomcorn millet as early as ~5500 BP, filling an important gap in archaeobotanical evidence from the western Loess Plateau. Further comparative analysis of multidisciplinary data suggests the shift in significance of these two millet crops during the late Neolithic may have been triggered by variations in human settlement intensity and climate change in the western Loess Plateau. The results of this study also suggest that the Banpo Phase of Yangshao Culture survived in the western Loess Plateau as late as ~5600 BP.